2021
DOI: 10.1097/sla.0000000000004815
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effectiveness of Diagnostic Tools to Establish the Presence of Peripheral Arterial Disease in People With Diabetes

Abstract: Objective: To evaluate the cost-effectiveness of point-of-care duplex ultrasound (PAD-scan) and other bedside tests for the diagnosis of peripheral arterial disease (PAD) in people with diabetes. Background: PAD is a risk factor for cardiovascular disease, diabetic foot ulceration (DFU), and amputation in diabetic patients. Diagnosis enables optimization of therapies to manage these risks. PAD-scan can be performed by frontline staff and has been shown to be the most accurate bedside test. However, its cost-ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…The recent Testing for Arterial Disease in Diabetes (TrEAD) study compared the diagnostic performance of bedside tests for the diagnosis of PAD in diabetes. 11 The results demonstrated that the visual waveform assessment is the most accurate 11 and cost-effective 12 diagnostic modality as compared with commonly used tests. However, the prognostic value of these tests in predicting wound healing remains unclear and has not been subject to a side-by-side comparison in the same group of patients.…”
Section: What This Study Addsmentioning
confidence: 93%
“…The recent Testing for Arterial Disease in Diabetes (TrEAD) study compared the diagnostic performance of bedside tests for the diagnosis of PAD in diabetes. 11 The results demonstrated that the visual waveform assessment is the most accurate 11 and cost-effective 12 diagnostic modality as compared with commonly used tests. However, the prognostic value of these tests in predicting wound healing remains unclear and has not been subject to a side-by-side comparison in the same group of patients.…”
Section: What This Study Addsmentioning
confidence: 93%
“…A literature review will be conducted to identify published health economic studies in similar patient groups. The structure and evidence that will be used in constructing the model will be determined following this review but may follow and update previous work by this group 14. Depending on ulceration status at presentation, this model classified patients into one of eight initial states following a test: true positive (with and without DFU), true negative (with and without DFU), false positive (with and without DFU) or false negative (with and without DFU).…”
Section: Methods and Analysismentioning
confidence: 99%
“…The structure and evidence that will be used in constructing the model will be determined following this review but may follow and update previous Open access work by group. 14 Depending on ulceration status at presentation, this model classified patients into one of eight initial states following a test: true positive (with and without DFU), true negative (with and without DFU), false positive (with and without DFU) or false negative (with and without DFU). It was assumed that true and false positive patients without DFU would be prescribed orthotics and additional foot checks, in addition to standard care.…”
Section: Health Economics Analysismentioning
confidence: 99%
See 2 more Smart Citations